Domain-agnostic procedural content generation can be done declaratively - Angilica, D; Germano, S; Ianni, G (CEUR Workshop Proceedings, 2023)
Procedural content generation is applied in the development process of many commercial games: au- tomatically generated contents are delivered to players in order to offer a constantly changing user experience and enrich the game itself. Designing algorithms for content generators can be a tedious job. The product of this work is often too domain specific and offers limited reusability and customizability. Declarative approaches to content generation, more properly defined as Declarative Content Specifica- tion (DCS) techniques, like the ones based on Answer Set Programming (ASP), promise to overcome some of these drawbacks, since they allow focusing on describing content requirements rather than programming ad-hoc generation engines. Also, DCS speed up the prototype generation techniques themselves. In turn, DCS techniques struggle to gain momentum mainly because of lack of integration with game engines. Furthermore, the promise of generality and reusability is neutralized by the burden of wiring and adapting declarative content specifications to the context of the game at hand. In this work, we report about our progress toward a general DCS module working in the Unity game engine, and integrated in an existing asset for declaratively defining AI modules. We illustrate both the design and runtime workflow of this module, and how game content developers could use it for devising their own content generation schemes. For this purpose, an example highlighting the advantages of this approach is described.